1974
DOI: 10.1037/h0036894
|View full text |Cite
|
Sign up to set email alerts
|

Effects of subject sophistication and evaluation apprehension on aggressive responses to weapons.

Abstract: Weber and Cook suggested that evaluation apprehension and subject sophistication are powerful determinants of behavior in the laboratory but that much of the evidence concerning subject sophistication (deception and/or demand awareness) has been confounded with evaluation apprehension, In the present study, there was an experimental manipulation in a 3 X 2 design of three levels of subject sophistication and two levels of evaluation apprehension in an otherwise close replication of the seven-shock-unassociated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0

Year Published

1976
1976
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 11 publications
7
43
0
Order By: Relevance
“…This outcome is partially or completely consistent with several other reports, including those by Buss et al (1972), Ellis et al (1971), Page and Scheidt (1971), and Turner and Simons (1974).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…This outcome is partially or completely consistent with several other reports, including those by Buss et al (1972), Ellis et al (1971), Page and Scheidt (1971), and Turner and Simons (1974).…”
Section: Resultssupporting
confidence: 82%
“…In fact, the results of the present study, as well as those of numerous other studies (e.g., Buss et al, 1972;Ellis et al, 1971;Page & Scheidt, 1971;Turner & Simons, 1974) indicate that the role of weapons in inhibiting violence seems to be at least as well documented as a weapons effect leading to aggression. A report in Psychology Today (Corey, 1979) also supported the possibility that weapons may inhibit violence in natural settings.…”
Section: Resultssupporting
confidence: 70%
“…Turner and Simons (1974;see also Simons & Turner, 1976) challenged Page and Scheidt's results, and Turner, Simons, Berkowitz, and Frodi (1977) even suggested, "Perhaps the failures to replicate the weapons effect occurred because the researchers used subjects who were not naïve about deception studies or who were very apprehensive about the impression they might create" (p. 369). Although Page and Scheidt and Turner et al disagreed over the issue of how experience with deception alters experimental performance, they agreed that it does have this potential.…”
Section: Christensen (1977)mentioning
confidence: 97%
“…Nevertheless, a trend is discernable. The more concrete the foreknowledge, the more it affects participants' behavior: When participants received detailed tip-offs about the true purpose of the experiment (e.g., Levy, 1967;Turner & Simons, 1974), or were explicitly told that they would be deceived (Finney, 1987), or explicitly acknowledged awareness of experimental manipulation (Golding & Lichtenstein, 1970), suspicion altered experimental performance (albeit not necessarily on all dependent measures). In contrast, when participants were merely informed that some kind of deception might happen (D. F. Allen, 1983;Finney, 1987;Wiener & Erker, 1986) or were told the purpose of the study (without indicating the possibility of deception; Gallo, Smith, & Mumford, 1973), their performance did not differ from that of control participants who were not given this information (but see Spinner, Adair, & Barnes, 1977).…”
Section: Wiener and Erker (1986)mentioning
confidence: 99%
“…Subjects who had been exposed to deception in previous social psychology experiments gave fewer shocks when exposed to guns in an aggressive context. Turner and Simons (1974) found that nonapprehensive subjects who knew the purpose of the weapons gave fewer shocks. An attempt by Halderman and Jackson (1979) to replicate the hornhonking study by Turner et al (1975) in a rural community did not support the weapons effect.…”
Section: Augusta College Augusta Georgiamentioning
confidence: 99%